The θ-twistor versus the supertwistor - Zheltukhin, A.A. (Вопросы атомной науки и техники, 2007)
We introduce the θ-twistor, which is a new supersymmtric generalization of the Penrose twistor and is also alternative to the supertwistor. The θ-twistor is a triple of spinors including the spinor θ extending the Penrose’s double of spinors. Using the θ-twistors yields an infinite chain of massless higher spin chiral supermultiplets (1/2,1), (1,3/2), (3/2,2),…,(S,S+1/2) generalizing the known scalar (0,1/2) supermultiplet.